PENGGUNAAN METODE LATIHANUNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN IPA SISWA KELAS VI SD NEGERI 001 UKUI SATUKECAMATAN UKUI - Suyatin (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The background of this study was the low science learning outcomes of sixth-grade students at SD Negeri 001 Ukui Satu, Ukui District. This research was conducted as a classroom action research in two cycles and aimed to improve science learning outcomes through the implementation of the training method. The data used in this study consisted of teacher activity data, student activity data, and students’ science (IPA) learning outcomes. The results showed that teacher and student activities, as well as science learning outcomes, improved in each cycle. This improvement was evidenced by: (a) increased teacher activity, where in the first cycle the teacher activity score was 19 (63%), categorized as fairly good, and in the second cycle it increased to 22 (73%), categorized as good; student activity also increased from a score of 47 (60%) in the first cycle, categorized as high, to a score of 52 (67%) in the second cycle, also categorized as high; and (b) improved science learning outcomes, as indicated by an increase in the number of students achieving the minimum mastery criterion (KKM), from 10 students (77%) in the first cycle to 11 students (85%) in the second cycle.